Pengaruh Gaya Kepemimpinan Directing Terhadap Kepuasan Kerja Karyawan Bank Mandiri Taspen - Ade Amellia Aprilysani; Tina Kartika; Andy Corry Wardhani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The directing leadership style is defined as a leadership approach where the leader provides clear, specific instructions and assumes a dominant role in decision-making, with minimal input from subordinates. This study seeks to examine the impact of the directing leadership style on employee job satisfaction at Bank Mandiri Taspen. The research adopts a quantitative methodology, with data collected through questionnaires administered to the entire population of employees at Bank Mandiri Taspen, comprising 19 respondents. The data were analyzed using simple linear regression and ANOVA, with statistical processing conducted via SPSS software. The results reveal that the ANOVA test produced a significance value of 0.04 (p < 0.05), indicating that the directing leadership style has a statistically significant effect on employee job satisfaction. The analysis further shows that the directing leadership style accounts for 48.4% of the variance in employee job satisfaction. Based on these findings, it can be concluded that the directing leadership style exerts a significant and measurable influence on employee job satisfaction at Bank Mandiri Taspen. These results underscore the importance of leadership style in shaping key organizational outcomes, particularly in the context of employee satisfaction.